Optimal Detection of Fusion Pore Dynamics Using Polarized Total Internal Reflection Fluorescence Microscopy - Nikolaus, Joerg; Hancock, Kasey; Tsemperouli, Maria; Baddeley, David; Karatekin, Erdem (Frontiers in Molecular Biosciences, 2021)
The fusion pore is the initial narrow connection that forms between fusing membranes. During vesicular release of hormones or neurotransmitters, the nanometer-sized fusion pore may open-close repeatedly (flicker) before resealing or dilating irreversibly, leading to kiss-and-run or full-fusion events, respectively. Pore dynamics govern vesicle cargo release and the mode of vesicle recycling, but the mechanisms are poorly understood. This is partly due to a lack of reconstituted assays that combine single-pore sensitivity and high time resolution. Total internal reflection fluorescence (TIRF) microscopy offers unique advantages for characterizing single membrane fusion events, but signals depend on effects that are difficult to disentangle, including the polarization of the excitation electric field, vesicle size, photobleaching, orientation of the excitation dipoles of the fluorophores with respect to the membrane, and the evanescent field depth. Commercial TIRF microscopes do not allow control of excitation polarization, further complicating analysis. To overcome these challenges, we built a polarization-controlled total internal reflection fluorescence (pTIRF) microscope and monitored fusion of proteoliposomes with planar lipid bilayers with single molecule sensitivity and ~15 ms temporal resolution. Using pTIRF microscopy, we detected docking and fusion of fluorescently labeled small unilamellar vesicles, reconstituted with exocytotic/neuronal v-SNARE proteins (vSUVs), with a supported bilayer containing the cognate t-SNAREs (tSBL). By varying the excitation polarization angle, we were able to identify a dye-dependent optimal polarization at which the fluorescence increase upon fusion was maximal, facilitating event detection and analysis of lipid transfer kinetics. An improved algorithm allowed us to estimate the size of the fusing vSUV and the fusion pore openness (the fraction of time the pore is open) for every event. For most events, lipid transfer was much slower than expected for diffusion through an open pore, suggesting that fusion pore flickering limits lipid release. We find a weak correlation between fusion pore openness and vesicle area. The approach can be used to study mechanisms governing fusion pore dynamics in a wide range of membrane fusion processes.